1997
DOI: 10.1002/eji.1830271018
|View full text |Cite
|
Sign up to set email alerts
|

A murine transmembrane tumor necrosis factor (TNF) transgene induces arthritis by cooperative p55/p75 TNF receptor signaling

Abstract: The arthritogenic activities of tumor necrosis factor (TNF) and its p55TNF-receptor (R) have been well documented in experimental animal models of arthritis, and in transgenic mice expressing wild-type or mutant transmembrane human TNF proteins in their joints. In this study we show that chronic inflammatory arthritis also develops in transgenic mice made to overexpress a mutant transmembrane from of the murine TNF protein (muTNF delta 1-12) which is known to utilize efficiently both the p55 and the p75TNFR. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(153 citation statements)
references
References 22 publications
8
143
0
2
Order By: Relevance
“…Generation, phenotypic and functional characterization of tmTNF mutant mice CCE (129Sv) ES cells were electroporated with a targeting vector containing a floxed neo cassette in the first intron of the murine TNF gene and the D1-12 mutation that encodes an uncleavable tmTNF protein [13,36] (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generation, phenotypic and functional characterization of tmTNF mutant mice CCE (129Sv) ES cells were electroporated with a targeting vector containing a floxed neo cassette in the first intron of the murine TNF gene and the D1-12 mutation that encodes an uncleavable tmTNF protein [13,36] (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work demonstrated that ectopic over-expression of human and mouse tmTNF can induce chronic arthritis in Tg mice [13]; however, the chimeric structure of the transgenes used in these studies, the increased copy number and the specific expression patterns attained precluded conclusive observations as to whether perturbations of endogenous tmTNF supports the development of arthritis. Furthermore, combinatorial inhibition of TACE and matrix metalloproteinases was reported to be highly effective in reducing collageninduced arthritis in mice [59], suggesting a possible non-pathogenic or even protective role of tmTNF in development of the disease.…”
Section: Tmtnf Supports Host Defenses Against Listeria Monocytogenes mentioning
confidence: 96%
See 2 more Smart Citations
“…149 It appears that local TNF is the driving force behind the chronic inflammation as it has been elegantly shown in arthritis models in transgenic and null mice where the immune system does not play an important role. [151][152][153][154] On the other hand it has also been shown that TNF plays an important role in the maturation of B cells and the formation of germinal centers 155 in mice. A chronic arthritis model has been developed by backcrossing a TCR V␤12 transgenic onto the DBA/1 background.…”
Section: Animal Models Of Arthritismentioning
confidence: 99%